2019
DOI: 10.3390/sports7120247
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Beliefs towards Sport Specialization, College Scholarships, and Financial Investment among High School Baseball Parents

Abstract: Adolescent athletes are increasingly encouraged to specialize in a single sport year-round in an effort to receive a college scholarship. For collegiate baseball, only 11.7 scholarships are available for a 35-player team. The beliefs of the parents of baseball athletes towards sport specialization are unknown, along with whether they have an accurate understanding of college baseball scholarship availability. The parents of high school baseball athletes were recruited to complete an anonymous questionnaire tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 26 publications
3
38
1
Order By: Relevance
“…In contrast, previous data suggest that only approximately 3% of high school basketball players will play college basketball, and even fewer will receive a scholarship to do so. 15 This finding is in agreement with previous studies of youth sport parents 21 and youth athletes, 6 which have found that parents and youth athletes overestimate their (or their child's) chances of receiving a college athletic scholarship. Therefore, there appears to be increasing evidence that a significant disconnect exists between parent knowledge regarding the availability of college athletic scholarships and parent belief in their child's receiving one of those rare scholarships.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, previous data suggest that only approximately 3% of high school basketball players will play college basketball, and even fewer will receive a scholarship to do so. 15 This finding is in agreement with previous studies of youth sport parents 21 and youth athletes, 6 which have found that parents and youth athletes overestimate their (or their child's) chances of receiving a college athletic scholarship. Therefore, there appears to be increasing evidence that a significant disconnect exists between parent knowledge regarding the availability of college athletic scholarships and parent belief in their child's receiving one of those rare scholarships.…”
Section: Discussionsupporting
confidence: 91%
“…1,19 Previous surveys of youth sport parents have identified a widespread belief that specialization is necessary for sport development and making a college team. 2,21 As a result of this widespread belief, youth sport is now a $15 billion industry that increasingly resembles professional sports, with athletes encouraged to specialize in a single sport year-round and the ultimate goal of receiving a college athletic scholarship. 1,11 The ability to specialize and participate year-round on club teams is the result of several factors, including the child's interest in a sport, the child's sport ability/talent, and family socioeconomic status (SES), which may limit opportunities for children from families with fewer resources to participate in youth sports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another contributor to early attrition in athlete populations is burnout. Athletic burnout has been defined as “a cognitive-affective syndrome comprised of emotional and physical exhaustion, a reduced sense of accomplishment, and sport devaluation.” 27 While burnout has been broadly discussed in the sport specialization literature, 5,47 few studies are available examining the link between specialization and burnout. In descriptive studies, Gustafsson et al 28,29 found that perfectionism and fear of failure were linked to higher levels of burnout among Scandinavian elite youth athletes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Swindell et al 56 described that early sport specialization among 303 Division I college athletes was uncommon, with the average age of specialization being about 15 years. As many parents and athletic entities (ie, club sports) justify single-sport specialization as the only means to achieve ''elite'' athletic potential, 17,43,47 more definitive and largescale study may be helpful to refine our understanding of the role of specialization in this population.…”
mentioning
confidence: 99%